An integrated information system to support supply chain management & performance in SMEs - Dekeng S. Budiarto; M. Agung Prabowo; Tutut Herawan (Journal of Industrial Engineering and Management (JIEM), 2017)
Purpose: This study aims to examine the relation between the level of supply chain management (SCM) adoption and small & medium enterprises (SMEs) performance. SCM adoption level is expected to facilitate SMEs in improving their efficiency, thus they can obtain their competitive advantage. Design/methodology/approach: This study uses primary data in the form of questionnaires. This study only takes the SMEs engaged in commerce (retail) business in order to avoid bias in IT usage. The questionnaires are given to 88 SMEs owners whom responsible for the IT development in their companies. Findings: The result proves that SCM adoption significantly affects SMEs performance. The hypotheses testing is performed using one-way ANOVA, the result shows that there are significant differences between level initiation, diffusion, and integration with SMEs performance. Originality: This study explains the relation between supply chain management (SCM) adoption level and SMEs performance that has never been performed before.
Keywords: 650; initiation; diffusion; integration; supply chain management; performance; SMEs